موقف الفكر الليبرالي الإندونيسي تجاه حقوق المرأة في القرآن : دراسة تحليلية نقدية /‏ - رتنا ديوي (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study aims to address the issue of the position of Indonesian Muslim liberalist toward women's rights in Qur'an. The study begins with the definition of liberal and its rise in Indonesia and its related terms; followed by an objective analysis of the liberal interpretation of women's rights such as the rights of women in society, inheritance, marriage, and divorce. This study relied on two methodologies, the inductive method and the analytical approach. The former is applied in collecting Quranic verses, which explain the issues regarding women's rights in Indonesian Muslim Liberalists movement based on various tafsir books, opinions; both classical and modern. The latter is implemented in analyzing Qur'anic texts and the scholars' views through the interpretation of Quranic verses and the prophetic ahadith. The researcher concluded that liberalist ideas on women's rights in Islam are contradictory since their interpretations are not in harmony with the message of the revelation. They consider the Qur'anic interpretations regarding this subject as irrelevant to the message of women's right in this modern era. The liberalists who do not recognize the equality of women and men mentioned in the Qur'an seek the alternatives ideas that shake the traditional basis of women's knowledge in Indonesia through publications; seminars, conferences, books and research articles.